1995
DOI: 10.1107/s0021889895007047
|View full text |Cite
|
Sign up to set email alerts
|

CRYSOL– a Program to Evaluate X-ray Solution Scattering of Biological Macromolecules from Atomic Coordinates

Abstract: A program for evaluating the solution scattering from macromolecules with known atomic structure is presented. The program uses multipole expansion for fast calculation of the spherically averaged scattering pattern and takes into account the hydration shell. Given the atomic coordinates (e.g. from the Brookhaven Protein Data Bank) it can either predict the solution scattering curve or fit the experimental scattering curve using only two free parameters, the average displaced solvent volume per atomic group an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

113
3,538
0
27

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,304 publications
(3,678 citation statements)
references
References 14 publications
113
3,538
0
27
Order By: Relevance
“…For macromolecules, we found that I(q) is well-represented by tens of points at small scattering amplitudes and up to hundreds of points at the larger values of q sampled in this study. When the number of grid points is not quite large enough, the current method seems to fail gracefully (the resulting error grows slowly with an increasing q), unlike the approach in which the scattering amplitude is expanded in terms of spherical harmonics (27).…”
Section: Methods and Theorymentioning
confidence: 89%
“…For macromolecules, we found that I(q) is well-represented by tens of points at small scattering amplitudes and up to hundreds of points at the larger values of q sampled in this study. When the number of grid points is not quite large enough, the current method seems to fail gracefully (the resulting error grows slowly with an increasing q), unlike the approach in which the scattering amplitude is expanded in terms of spherical harmonics (27).…”
Section: Methods and Theorymentioning
confidence: 89%
“…In each MD trajectory, after a rapid rise in the first 2 ns, the RMSD evolved towards a stable value near 2.5 nm and the R g value decreases. Twothousand four-hundred conformers were obtained as snapshots taken at regular interval (50 ps) along the six first MD simulations, and the theoretical scattering profiles were calculated from the structures using the programme CRYSOL 58 and compared with the experimental data. The best agreement with the experimental curve yielded a w-value of 6, down from a value of 10 calculated for the initial structure.…”
Section: Methodsmentioning
confidence: 99%
“…For each of the 20 energy-minimized models, 140 models were generated with the torsion-based random conformational search functionality of Another Molecular Mechanics Program (AMMP) implemented in VEGA ZZ, leading to 2,800 additional conformers. A model with a w-value of 2.8 between the experimental and calculated curve was finally selected using CRYSOL 58 (Fig. 2).…”
Section: Methodsmentioning
confidence: 99%
“…33 Calculated form factors for BPTI monomer and decamer were obtained using the CRYSOL program 55 from a set of crystallographic coordinates (PDB entry 1BHC 34 ). At very low scattering vectors, (s < 0.02 Å -1 ), interparticle interactions may perturb the scattering intensity and affect the form factor.…”
Section: Simulation Procedures 4321 Form Factorsmentioning
confidence: 99%